A new multifunctional fluorescent molecule for highly efficient non-doped deep-blue electro-fluorescence with high color-purity and efficient phosphorescent OLEDs. Issue 2 (12th December 2022) - Xu, Lei; Sun, Mizhen; Zhou, Yannan; Lou, Jingli; Xie, Mingliang; Li, Zipeng; Sun, Qikun; Pan, Yuyu; Xue, Shanfeng; Yang, Wenjun
Abstract : A multifunctional molecule DTPCZTZ was synthesized, which can not only realize high efficiency nondoped deep blue device, but also achieve high efficiency phosphorescent devices. Abstract : High efficiency and high color purity are two key factors for achieving non-doped deep-blue organic light-emitting diodes (OLEDs). Herein, a novel emitter 3, 6-di- tert -butyl-9-(4′-(4, 5-diphenyl-4 H -1, 2, 4-triazol-3-yl)-[1, 1′-biphenyl]-4-yl)-9 H -carbazole (DTPCZTZ ) with a weak donor–acceptor structure containing carbazole as the donor and triazole as the acceptor was designed and synthesized. Photophysics and theoretical calculation show that it has the hybridized local and charge-transfer (HLCT) state. A subtle introduction of tert -butyl on carbazole combined with twisted 3, 4, 5-triphenyl-4 H -1, 2, 4-triazole endows the molecule with a highly twisted molecular conformation, and it successfully achieves a deep-blue emission. And the non-doped device based on DTPCZTZ showed a electroluminescence (EL) peak at 424 nm, the Commission Internationale de L'Eclairage (CIE) coordinates of (0.17, 0.06), and the maximum external quantum efficiency (EQEmax ) up to 7.6%, and is one of the best non-doped OLEDs with pure organic deep-blue HLCT molecules. Importantly, the application potential of DTPCZTZ in phosphorescent OLEDs (PhOLEDs) is also evaluated based on Ir(PPy)2 (acac) and Ir(MDQ)2 (acac) as the dopants and DTPCZTZ as the host, and high-efficiency green and red PhOLEDs with an EQEmax, maximum power efficiency (PEmax ), maximum current efficiency (CEmax ), and maximum luminance ( L max ) of up to 20.1%, 81.5 lm W −1, 72.6 cd A −1, and 29 595 cd m −2 and 15.3%, 22.1 lm W −1, 21.1 cd A −1, and 10 526 cd m −2, respectively, were successfully realized. These results provide a valuable strategy for the design of highly efficient deep-blue emitters and using them as host materials, having significant potential for practical applications.